Accessibility of Referent Information Influences Sentence Planning: An Eye-Tracking Study - Ganushchak, Lesya Y.; Konopka, Agnieszka E.; Chen, Yiya (Frontiers in Psychology, 2017)
This study investigated the time-course of online sentence formulation (i.e., incrementality in sentence planning) as a function of the preceding discourse context. In two eye-tracking experiments, participants described pictures of transitive events (e.g., a frog catching a fly). The accessibility of the agent (Experiment 1) and patient (Experiment 2) was manipulated in the discourse preceding each picture. In the Literal condition, participants heard a story where the agent or patient was mentioned explicitly (fly, frog). In the Associative condition, the agent or patient was not mentioned but was primed by the story (via semantically or associatively related words such as insect, small, black, wings). In the No Mention condition, the stories did not explicitly mention or prime either character. The target response was expected to have the same structure and content in all conditions (SVO sentences: The frog catches the fly). The results showed that participants generally looked first at the agent, before speech onset, regardless of condition, and then at the patient around and after speech onset. Analyses of eye movements in time windows associated with linguistic planning showed that formulation was sensitive mainly to whether the agent was literally mentioned in the context or not and to lesser extent to conceptual accessibility (Experiment 1). Furthermore, accessibility of the patient (be it literal mention of its name or only availability of the concept) showed no effect on the time-course of utterance planning (Experiment 2). Together, these results suggest that linguistic planning before speech onset was influenced only by the accessibility of the first character name in the sentence, providing further evidence for highly incremental planning in sentence production.